New era of personalised epilepsy management. (9th October 2020) - Chen, Zhibin; Rollo, Ben; Antonic-Baker, Ana; Anderson, Alison; Ma, Yuanlin; O'Brien, Terence J; Ge, Zongyuan; Wang, Xuefeng; Kwan, Patrick
Abstract : The trial and error approach to epilepsy treatment has not changed for over a century but machine learning and patient derived stem cells promise a personalised and more effective strategy, argue Patrick Kwan and colleagues